(untitled) (The Pretoria Student Law Review, 2021)
Media freedom is the capacity of the media to act as a barometer to call government to account vis-à-vis the Constitution of Kenya, 2010 especially the values, spirit and ethos enshrined therein. So much so that countries which are strong democracies always have strong and free media. A free and democratic society is not possible without an independent, free and responsible media and an active civil society. Freedom House Report results from the fact that Kenya currently finds itself in a very interesting position where media freedom exists boldly on paper, but the reality on the ground is something else. The current Constitution of Kenya which came into force on 27 August 2010, has not only been hailed as reformist, but it has a new and progressive Bill of Rights requiring extensive reforms to both the media and information management frameworks. However, the government seems to have another agenda. As will be observed below, the government has introduced several laws that, on the outside appear to be progressive and in line with the new Constitution, but upon closer inspection clearly has an agenda that undermines media freedom in Kenya. In the sections which follow, this paper will analyse the legal framework and social factors relevant to media freedom in Kenya.